2012
DOI: 10.1159/000342624
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Health of Children with Type 1 Diabetes Mellitus in Kuwait: A Case-Control Study

Abstract: Objective: The aim of this study was to evaluate periodontal health in children diagnosed with type 1 diabetes mellitus. Subjects and Methods: Periodontal health was clinically examined and compared in 95 children diagnosed with type 1 diabetes and 61 healthy control subjects (4–14 years old). Plaque index, gingival index, clinical attachment loss and bleeding on probing were assessed on the 6 Ramfjord index teeth. Diabetes history was recorded based on information provided by the physician from the medical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 57 publications
3
51
1
2
Order By: Relevance
“…Thus, from the findings in the present group of individuals there was no clear effect of glycaemic control on the level of gingival inflammation. This is in contrast to other studies, which found that diabetic children have significantly higher gingival bleeding index scores than the healthy population 7,[42][43][44][45][46][47] . Nevertheless, one should bear in mind that in the current analysis, most of the individuals with TIDM had HbA1c values between 5.9% and 9% (only 7 of 74 patients had an HbA1c value above 9%), indicating relatively good metabolic control for the patients in the pediatric diabetes clinic.…”
Section: Discussioncontrasting
confidence: 98%
“…Thus, from the findings in the present group of individuals there was no clear effect of glycaemic control on the level of gingival inflammation. This is in contrast to other studies, which found that diabetic children have significantly higher gingival bleeding index scores than the healthy population 7,[42][43][44][45][46][47] . Nevertheless, one should bear in mind that in the current analysis, most of the individuals with TIDM had HbA1c values between 5.9% and 9% (only 7 of 74 patients had an HbA1c value above 9%), indicating relatively good metabolic control for the patients in the pediatric diabetes clinic.…”
Section: Discussioncontrasting
confidence: 98%
“…The higher number of children who brush their teeth once a day was found higher among children with type 1 diabetes. Our finding regarding brushing habits among children are comparable with other studies reported [12,31].…”
Section: Discussionsupporting
confidence: 92%
“…The increased risk for periodontal disease among children with diabetes has been reported in dental literature. Furthermore, periodontal destruction that starts at an early age becomes more evident during adolescence and screening programmes for early detection of people at risk should be considered routine for diabetic patients.…”
Section: Discussionmentioning
confidence: 94%